Closed hyperthermic intraperitoneal chemotherapy with CO2 recirculation system compared with the open Coliseum technique in peritoneal malignity treatment. (February 2023) - Diaz, Eduardo; Fabra, Isabel; Vicente, Emilio; Quijano, Yolanda; Duran, Hipolito; Malave, Luis; Ruiz, Pablo; Costantini, Giulia; Nola, Valentina; Caruso, Riccardo; Ferri, Valentina
Abstract: Background: Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) for peritoneal carcinomatosis can be performed in two ways: first, the standard open abdominal technique (Open HIPEC); or second, the closed technique. In recent years, a new technique has been introduced to perform closed HIPEC; the Peritoneal Recirculation System (PRS-1.0 Combat) with CO2 recirculation technology (PRS Closed HIPEC). The objective of this study is to present our experience with the PRS Closed HIPEC by comparing the intraoperative, postoperative and oncological results with the standard Open HIPEC technique (the Coliseum technique). Methods: Data on patients undergoing CRS and HIPEC at the Sanchinarro University Hospital, Madrid from October 2012 to June 2021 were collected in a prospective database. The inclusion criteria were patients with primary or recurrent peritoneal metastases in gastrointestinal malignancies or ovarian cancer. The presence of an unresectable peritoneal carcinomatosis, the coexistence of another oncological disease, unresectable and distant metastases were the exclusion criteria. Results: From October 2014 to June 2021, 84 patients underwent CRS and HIPEC at the Sanchinarro University Hospital, Madrid with curative intent. Since the introduction of the PRS Closed HIPEC technique in 2016, 65 patients have been treated. Before the introduction of PRS Closed HIPEC, 19 cases were performed using the Coliseum technique (the Open HIPEC group). The intraoperative results were similar in the two groups. Complete cytoreduction was achieved in all cases in the Open HIPEC group and in 98% in the PRS Closed HIPEC group. The rate of major complications was similar between the groups. Median Overall Survival (OS) resulted better in the Closed HIPEC group (67 months) with respecto to the Open group (43 months) (p < 0, 001). Median Disease-Free Survival (DFS) was 15 months in the Open HIPEC group and 40 months in the PRS Closed HIPEC group (p < 0.001). Conclusion: The Peritoneal Recirculation System with CO2 recirculation technology (PRS Closed HIPEC) is a reproducible and safe technique and may represent a valid alternative for the administration of HIPEC. Highlights: Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is the treatment of choice in peritoneal carcinomatosis. The Closed HIPEC technique was introduced due to the need to improve the safety of the staff in the operating room. The PRS Closed HIPEC creates a turbulent flow with CO2 recirculation that allows an optimal diffusion and penetration of the cytotoxic drug. The PRS Closed HIPEC technique with CO2 recirculation could achieve better local control in the treatment of peritoneal malignancies compare with Open HIPEC techniques.